Someone it is Good to Argue With - Xie, Yun; Wang, Yiran (Informal Logic)

(untitled) (Informal Logic, 2026)
This paper discusses virtuous audiences in argumentation, asking “what does the virtuous audience look like”, and “how could they contribute to a fully satisfying argument”? We first propose to conceive the role of audience in a moderate way, as someone who is addressed by the arguer. Then, we argue that an audience would participate in and contribute to an argument by listening and responding to the arguer, and then by improving themselves. On that basis, we develop a conception of the virtuous audience and make a list of virtues that the virtuous audience needs to cultivate. Finally, we take the list as a framework for analyzing different ways in which the audience can behave badly when participating in argumentation.